A study on following behavior based on the time headway - Khansari, Ehsan Ramezani; Tabibi, Masoud; Nejad, Fereidoon Moghadas (Penerbit Universiti Kebangsaan Malaysia, 2020)
While time headway (TH) is a relatively simple variable and has been well researched, it has been less explored in non-lane-based traffic. The main aim of this paper is considering lateral distance in studying TH in a non-lane-based traffic flow. In this study driving behavior, speed-TH relationship, and the following threshold by using only TH in a non-lane-based flow were investigated. In a novel approach, THs were segmented into five intervals in a step by step manner from smallest to largest THs. Considering lateral distance led to divide driving behavior into intervals (based on the average TH), including: Unsafe (0-0.7 sec), non-lane-based car-following (0.9 sec), lane-based car-following (1.0 sec), overtaking TH (1.3 sec), and free driving (larger than 2.5 sec). It was founded that the TH of starting overtaking maneuver can be a good criterion to distinguish between following and free driving behavior. Also, in lane-based car-following behavior, when lateral distance between the following and preceding vehicles was not considerable, the smallest THs were seen. It has happened around the average speed of the flow as the driver may adopt lower THs because of the tendency to overtaking. Linear relationship was found between TH and lateral distance in non-lane-based car-following conditions. TH of non-lane-based behavior is less than lane-based and smaller THs would force drivers to apply lateral distance or vice versa.